THE ROLE OF FUZZY LOGIC SYSTEMS FOR CONTROL OF THE PNEUMATIC VALVE OF BOTTLE WASHER IN BEVERAGE COMPANIES, SPECIFICALLY THE KRONES GROUP OF COMPANIES. - T., Mushiri; N., Chirinda, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Intelligent systems have greatly contributed in automating the process segments that includes the maintenance function in the manufacturing industries. The purpose of this research was to come up with an intelligent monitoring tool to reduce the number of breakdowns in Krones machinery (selected the bottle washer as a study sample). The objective of the research was motivated by an appreciation of considering Human Machine Interface (HMI) and automatic monitoring of the plant while in the office. The case of a local beverage manufacturer (anonymous) was used who has installed a bottle washer of this nature. The research entirely was centred on Krones machinery in order to model around similar operational conditions regarding their design orientation and function embedded within them. The Fuzzy Logic system was derived among other Artificial Intelligent systems to be best appropriate to solve the breakdown challenges automatically. Total breakdown of the bottle washer was realised at any time it would experience a minor failure. The bottle washer is complex so much that it is not easy to carry out a successful troubleshooting. For instance, the pneumatic valve could just stick and cause production to stop immediately. The researchers carried out a company audit, interviews and questionnaires in order to gather relevant data. Different data analysis techniques were used such as Ishikawa diagram. The results of which were used in intelligent condition-based-maintenance modelling to solve the problem using fuzzy logic system. MATLAB software was used as a means for data modelling and manipulation. The researchers recommend the use of this intelligent monitoring tool to all beverage manufacturers who have installed the krones machinery. This will increase productivity, reduce number of breakdowns, increase plant availability and lean maintenance will inevitably be applied to the bottle washer.